MODELING OF PROFESSIONAL TRAINING OF PEDAGOGICAL STAFF IN CLASSICAL UNIVERSITIES - Москаленко, Алла (Київський національний університет імені Тараса Шевченка, 2022)
The article presents the development of a model of professional training of teachers in classical universities with the identification of the main key positions: in classical education most fully and effectively combine all aspects of quality training of teachers; the model is a formalized structure that will work only if it is filled with content; the model is fundamental, integrative and modernizing at the same time, to include target, theoreticalmethodological, semantic, organizational-technological and criterion-estimating structural blocks which allow to structure and specify: the purposeof the task, methodological approaches, the maintenance of structural components, principles of the form, methods, means, methods, stages, functions, pedagogical conditions, criteria and indicators of diagnostics of the level of formation of professional competence of pedagogical staff, levels and result; training of pedagogical staff in classical universities is defined as the most important and system-forming function of a higher education institution that ensures equality of education: pre-vocational training; professional training; postgraduate training, that in a complex provide the level of development of professional competence of pedagogical staff corresponding to requirements of the standard.The proposed author's model corresponds to the identified trends in the coordination of changes in pedagogical activities, requirements for professional training of teachers in accordance with the standard of higher education in the profession "Teacher of general secondary education"; opens opportunities for the development of similar models of training specialists in other specialties in classical universities.

Представлено розробку моделі професійної підготовки педагогічних кадрів у класичних університетах із виокремленням основних ключових позицій: у класичній освіті найбільш повно й ефективно поєднано всі грані якісної підготовки педагогічних кадрів; модель є формалізованою структурою, фундаментальною, інтегративною та модернізаційною одночасно, включає цільовий, теоретико-методологічний, змістовий, організаційно-технологічний та критеріально-оцінювальний структурні блоки. Запропонована авторська модель відповідає виявленим тенденціям до узгодження змін у педагогічній діяльності, вимог до професійної підготовки педагогічних кадрів відповідно до стандарту вищої освіти за професією "Вчитель закладу загальної середньої освіти"; відкриває можливості для розробки подібних моделей підготовки фахівців інших спеціальностей у класичних університетах.
МОДЕЛЮВАННЯ ПРОФЕСІЙНОЇ ПІДГОТОВКИ ПЕДАГОГІЧНИХ КАДРІВ У КЛАСИЧНИХ УНІВЕРСИТЕТАХ